My Health Companion©: A Low-Tech Personal Health Record Can Be an Essential Tool for Maintaining Health - Clarann Weinert; Shirley Cudney (Rural Nurse Organization; Binghamton University, 2012)
Objective: To report the initial evaluation of a personal health record (My Health Companion© (MHC©) developed to help individuals track, maintain, and appropriately communicate health information. Design and Sample: Data were examined from three rural independent studies in which MHC© was used: Women to Women (N = 94); Enhancing Self Care (N=41); and Health Enhancement for Rural Elderly (N=33). Measurements: Tools were the Perceived Self-Efficacy in Interacting with Healthcare Providers (PEPPI) scale and research team-generated questions related to the level of use, helpfulness in health maintenance activities, suggestions for improvement, and whether or not the MHC© would be recommended to others. Results: The PEPPI scores indicated that use of the MHC© contributed to enhanced perceived self-efficacy and answers to questions suggested the MHC© was helpful in promoting health maintenance activities and would be recommended to others. Valuable suggestions for improvement were offered by the participants. The ratings of level of use of the MHC© were relatively low. Conclusions: By documenting key health information in a relatively simple, organized fashion, individuals can collect, track, and share health information that will promote prevention or early identification of health problems and foster productive partnerships with their healthcare providers. Key Words: Personal Health record, Self-care Management, Chronic illness, Client/provider Relationships, Rural